Application of random mutagenesis to enhance the production of polyhydroxyalkanoates by Cupriavidus necator H16 on waste frying oil - Obruca, Stanislav; Snajdar, Ondrej; Svoboda, Zdenek; Marova, Ivana (World journal of microbiology & biotechnology, 2013)
Using random chemical mutagenesis we obtained the mutant of Cupriavidus necator H16 which was capable of improved (about 35 %) production of poly(3-hydroxybuytrate) (PHB) compared to the wild-type strain. The mutant exhibited significantly enhanced specific activities of enzymes involved in oxidative stress response such as malic enzyme, NADP-dependent isocitrate dehydrogenase, glucose-6-phosphate dehydrogenase and glutamate dehydrogenase. Probably, due to the activation of these enzymes, we also observed an increase of NADPH/NADP⁺ ratio. It is likely that as a side effect of the increase of NADPH/NADP⁺ ratio the activity of PHB biosynthetic pathway was enhanced, which supported the accumulation of PHB. Furthermore, the mutant was also able to incorporate propionate into copolymer poly(3-hydroxybuytyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] more efficiently than the wild-type strain (Y3HV/prec = 0.17 and 0.29 for the wild-type strain and the mutant, respectively)). We assume that it may be caused by lower availability of oxaloacetate for the utilization of propionyl-CoA in 2-methylcitrate cycle due to increased action of malic enzyme. Therefore, propionyl-CoA was incorporated into copolymer rather than transformed to pyruvate via 2-methylcitrate cycle. Thus, the mutant was capable of the utilization of waste frying oils and the production of P(3HB-co-3HV) with better yields and improved content of 3HV resulting in better mechanical properties of copolymer than the wild-type strain. The results of this work may be used for the development of innovative fermentation strategies for the production of PHA and also it might help to define novel targets for the genetic manipulations of PHA producing bacteria.
Keywords: olej z řepky; Polyhydroxyalkanoates; Industrial Waste; Mutagenesis; mutageneze; Fatty Acids, Monounsaturated; acylkoenzym A; Oxidative Stress; bioreaktory; Biosynthetic Pathways; polyhydroxyalkanoáty; Bacterial Proteins; Fermentation; Acyl Coenzyme A; Plant Oils; oleje rostlin; biosyntetické dráhy; bakteriální proteiny; průmyslový odpad; Rapeseed Oil; Brassica rapa; oxidační stres; Polyesters; Cupriavidus necator; polyestery; Bioreactors; hydroxybutyráty; kyseliny mastné mononenasycené; Hydroxybutyrates; fermentace